Diphospholyl and triphospholyl zirconium pi-complexes: Ziegler-Natta oligomerization catalysts and reactive intermediates in P-C cage formation by hydrolysis - Panhans, Jürgen; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Journal of Organometallic Chemistry, 2009)
2,4,5-Tri(t-butyl)-1,3-diphospholyl sodium salt (2a) and 3,5-di(t-butyl)-1,2,4-triphospholyl sodium salt (3a) react with ZrCl(4) and CpZrCl(3) to form (eta(5)-2,4,5-tri(t-butyl)-1,3-diphospholyl)ZrCl(3) (4), Cp(eta(5)-2,4,5-tri( t-butyl)-1,3-diphospholyl)ZrCl(2) (5), and Cp(eta(5)-3,5-di(t-butyl)-1,2,4-triphospholyl) ZrCl(2) (6) in the complete absence of water, respectively. Surprisingly, bent sandwich complex 6 exhibits the NMR spectroscopic characteristics of a hindered ring ligand rotation but the cyclopentadienyl ligand of 5 rotates freely in the NMR time scale in spite of the superior space demand of its 2,4,5-tri(t-butyl)-1,3-diphospholyl ligand. This contradiction is discussed on the basis of an attractive interligand P-C interaction between homo- and heterocyclic pi-ligands, which is stronger for 6. Water even in trace amounts present in the reaction mixture changes the course of the reactions completely. No zirconium p-complexes are accessible this way, but only oligo- or polycyclic organophosphorus compounds. Compound 3a and ZrCl(4) form the asymmetric tricyclic P(6)(t-BuC)(4)H(2) isomer 8 with two P=C double bonds as a dimer of 1,2,4-triphosphol. It is accompanied by small amounts of HCl addition product 9, where one of the P=C double bonds is eliminated. Compound 8 contains six, and 9 eight stereogenic centers, but both form one pair of enantiomers each only. A single stereoisomer of P(6)(t-BuC)(4)H(2) cage 10 is formed if (1-trimethylstannyl)-3,5- di(t-butyl)-1,2,4-triphosphol 3b is used as the P(3)(t-BuC)(2) source in combination with Cp*ZrCl(3) in the presence of trace amounts of water. Compound 10 is a meso-compound, which is composed by dimerization of either two homochiral units of (R)-3,5- di(t-butyl)-1,2,4-triphosphol 3cR or by two units of its S-enantiomer 3cS. No trace of cyclic addition products has been identified, which would represent the heterochiral combination of enantiomers 3cR + 3cS. P2- and P3-zirconocene dichloride derivatives 5 and 6 have been tested as Ziegler-Natta alkene oligomerization catalysts. Both are catalytically active with 1-hexene as the substrate, but cannot compete with the activity of the phosphorus-free original catalyst Cp(2)ZrCl(2). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Phosphorus; Zirconium; pi-Complex; Ziegler-Natta catalyst; P-C cage compounds